High-toughness and high-modulus aluminum-based composite material and preparation method thereof

The aluminum alloy components are designed through alloying and composite, and specific elements and SiC ceramic particles are added to the aluminum matrix. The aluminum-based composite material is prepared by hot press sintering assisted semi-solid stirring casting method, which solves the problem of insufficient performance of aluminum alloys in complex environments and realizes high strength and high modulus material preparation.

CN119640083AActive Publication Date: 2025-03-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202411555543.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Existing aluminum alloys have insufficient performance in complex and harsh environments, especially inconsistencies in strength and toughness and modulus, resulting in prone to failure at high temperatures.

Method used

Through alloying and composite, the components are designed to form heat-resistant L phase and L12 phase as the main precipitation phase, and Cu, Mg, Re and Zr elements, as well as micron and nanoscale SiC ceramic particles, were added to the aluminum alloy matrix, and prepared by hot press sintering assisted semi-solid stirring casting.

Benefits of technology

The preparation of high-strength, tough and high-modulus aluminum-based composite materials has been achieved, which significantly improves the mechanical properties and high temperature stability of the material, and solves the problem of insufficient performance of aluminum alloys in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640083A_ABST
    Figure CN119640083A_ABST
Patent Text Reader

Abstract

The invention relates to the field of special aluminum-based composite materials, and discloses a high-toughness and high-modulus aluminum-based composite material and a preparation method thereof.The method comprises the steps that SiC ceramic particles and aluminum powder are mixed and subjected to ball milling in a vacuum ball milling tank, and then an aluminum-based composite material precursor is prepared through cold pressing and vacuum sintering; smelting the aluminum-based composite material precursor, a 6061 aluminum alloy cast ingot and a material containing Cu, Mg, Re (La / Ce = 3 / 2) and Zr elements in a smelting furnace, cooling to a semi-solid temperature interval after the aluminum-based composite material precursor is in a molten state, and stirring the aluminum-based composite material precursor, the 6061 aluminum alloy cast ingot and the material; and heating to 740-760 DEG C, carrying out ultrasonic vibration after a molten state, and finally, carrying out casting and pressure casting treatment to obtain the high-toughness and high-modulus aluminum-based composite material. According to the method, during smelting, semi-solid stirring and high-power ultrasonic treatment are introduced, uniform distribution of SiCp in a melt is achieved, and macro-quantity preparation of the high-toughness and high-modulus aluminum-based material is achieved by comprehensively considering the mechanism that the alloying elements and the content and size of SiCp affect the mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of special aluminum-based composite materials, and in particular to a high-strength and high-modulus aluminum-based composite material and a preparation method thereof. Background Art

[0002] High-strength aluminum-based materials are key lightweight components for the rapid development of aerospace vehicles such as rockets and spacecraft. However, due to the uncoordinated strength and toughness, low modulus and severe high-temperature softening of conventional commercial aluminum alloys, they are prone to failure in complex service environments. Studies have shown that by adding other alloying elements to the aluminum matrix and high-strength, high-modulus ceramic particles to form advanced special aluminum-based composite materials with complementary advantages, the performance of the aluminum alloy matrix can be significantly improved. Based on this, the present invention proposes to achieve the preparation of special aluminum-based composite materials with high strength and toughness, high modulus, through alloying and compounding, and develop an excellent method for preparing aluminum-based composite materials, so as to solve the problem of insufficient performance of aluminum alloys in complex and harsh environments.

[0003] In terms of alloying, in order to improve the performance of the material, it is necessary to reduce the coarsening tendency of the second phase and consider the L phase (AlMg) with better heat resistance when designing the composition. 4 Si 3 Cu) and L1 2 The L phase is the main precipitation phase. Therefore, commercial 6061 aluminum ingot is used as the matrix alloy, and Cu is appropriately added to significantly promote the formation of L phase, change the precipitation phase type, and significantly improve the mechanical properties of the material. Mg has a high binding energy with vacancies. The presence of Mg at the grain boundary can capture dislocations and promote grain boundary nucleation. To a certain extent, it can weaken the formation of the non-precipitation zone, thereby improving the strength of the material. In addition, Mg is easy to form in SiC p In order to achieve significant grain refinement and prevent thermal cracking, Re (La, Ce) is selected as a nucleating agent, which can form a thermodynamically stable L1 2 Ordered phase (Al 3 Considering the relatively high diffusion rate of Re in Al, Al 3 Re may coarsen at high temperatures (e.g., 300-400°C), while Zr has a low diffusion rate in Al. Therefore, Zr is added to Al to form L1 in situ. 2 Ordered Re / Zr-rich Al 3 (Re, Zr) to resist the coarsening tendency.

[0004] In terms of composites, compared with traditional aluminum, the development of aluminum-based composite materials (AMCs) has effectively solved the shortcomings of poor mechanical properties of aluminum. At the same time, AMCs have higher specific strength and specific stiffness, good high temperature stability, lower linear expansion coefficient and excellent wear resistance, and have broad application prospects in aerospace, automobile transportation, and electronic 3C fields. SiC p It is an excellent reinforcement material with the advantages of high modulus (400GPa), high hardness (3400HV), high wear resistance, low density, good thermal stability, not easy to crack, and no reaction with aluminum matrix. In addition, the introduction of nano reinforcement not only shows a good strengthening effect, but also maintains the initial toughness of the matrix, effectively balancing the contradiction between the strength and plasticity of traditional AMCs. Based on the consideration of improving the comprehensive mechanical properties of composites, micron-sized SiC p With Nano-SiC p The hybrid is added as a reinforcement into the aluminum alloy matrix to prepare a composite material, in order to improve its strength and modulus without damaging the plasticity of the material, so as to achieve excellent comprehensive mechanical properties. Summary of the invention

[0005] Combined with the special requirements of the composite material itself, the raw materials are selected based on the research status of the aluminum alloy matrix, and the alloying elements and SiC are comprehensively considered. p The influence of content and size on mechanical properties is studied, and efforts are made to achieve large-scale preparation of high-strength, high-modulus materials. Stir casting is widely used due to its advantages such as fewer process steps, simple equipment, easy molding, low cost, and ability to achieve large-scale preparation of ingots. However, conventional stirring casting is difficult to process high-content SiC p It is difficult to disperse nano-SiC p Add to aluminum melt. Based on this, the present invention provides a hot pressing sintering assisted semi-solid stirring casting method for preparing high-strength, high-modulus aluminum-based composite materials. The present invention uses the SiC ceramic particles (SiC p ) and aluminum powder by high-energy ball milling to initially disperse SiC p And make composite material prefabricated block, reach SiC p Good interface bonding with Al, while ensuring that the density during smelting is close to that of aluminum-based melt; during smelting, high-speed semi-solid stirring and high-power ultrasonic treatment are introduced to achieve SiC p Evenly distributed in the melt.

[0006] To achieve the above object, on the one hand, the present invention provides a method for preparing a high-strength, high-modulus aluminum-based composite material, which comprises the following steps:

[0007] S1, mixing SiC ceramic particles with aluminum powder, ball milling in a vacuum ball mill under an argon protective atmosphere, and then cold pressing and vacuum sintering to prepare an aluminum-based composite material precursor;

[0008] The mass ratio of SiC ceramic particles to aluminum powder is 1:4 to 1:5, and the SiC ceramic particles are micron SiC with a mass ratio of 5:1. p With Nano-SiC p ;

[0009] S2. Under an argon protective atmosphere, the aluminum-based composite material precursor prepared in step S1, the 6061 aluminum alloy ingot, and the materials containing Cu, Mg, Re (La / Ce=3 / 2), and Zr elements are melted in a melting furnace at a temperature of 800° C. After becoming molten, the temperature is lowered to a semi-solid temperature range of 600-630° C. to obtain a semi-solid melt and stirred to fully and evenly disperse the SiC ceramic particles; then the temperature is raised to 740-760° C., and after the semi-solid melt is transformed into a molten state, the SiC ceramic particles are evenly distributed in the aluminum melt by ultrasonic vibration, and finally, high-strength, high-modulus aluminum-based composite materials are obtained by casting and die-casting;

[0010] Among them, the added micron SiC p With Nano-SiC p They account for 5wt% and 1wt% of the 6061 aluminum alloy ingot respectively, and the added Cu, Mg, Re (La / Ce=3 / 2) and Zr elements account for 4wt%, 1wt%, 0.5wt% and 0.2wt% of the 6061 aluminum alloy ingot respectively. The Cu element is selected from Al-50Cu master alloy, the Mg element is selected from pure magnesium ingot, the Re element is selected from Al-10Re master alloy, and the Zr element is selected from Al-10Zr master alloy.

[0011] The present invention adopts the existing conventional 6061 aluminum alloy ingot, and its main components are shown in Table 1:

[0012] Table 1

[0013]

[0014] As a further preferred technical solution of the present invention, in step S1, micron SiC p The particle size is 3-8um, nano SiC p The particle size is 40-80nm.

[0015] As a further preferred technical solution of the present invention, in step S1, the parameters for ball milling SiC ceramic particles and aluminum powder are: rotation speed 220 rpm, time 15 hours, and alternating clockwise and counterclockwise rotation every hour, with a rest period of 30 minutes in between.

[0016] As a further preferred technical solution of the present invention, in step S1, the cold pressing pressure is 60 MPa and the vacuum sintering temperature is 540°C.

[0017] As a further preferred technical solution of the present invention, in step S2, the aluminum-based composite material precursor is placed at the bottom of the 6061 aluminum alloy ingot.

[0018] As a further preferred technical solution of the present invention, in step S2, the stirring speed is 400-700 rpm.

[0019] As a further preferred technical solution of the present invention, in step S2, an ultrasonic horn is used for ultrasonic vibration. The ultrasonic horn is located 2 to 5 cm below the liquid surface, the ultrasonic frequency is 18 to 20 kHz, the power is 3000 W, and the treatment time is 5 to 10 minutes.

[0020] As a further preferred technical solution of the present invention, in step S2, the pressure of the die-casting process is 400 kN, and the holding time is 2 to 5 minutes.

[0021] According to another aspect of the present invention, the present invention also provides a high-strength, high-toughness, high-modulus aluminum-based composite material, which is prepared by the above method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention adopts the previous SiC p High-energy ball milling with aluminum powder to initially disperse SiC p , and then prepare the composite prefabricated block to achieve SiC p Good interface bonding with Al, while ensuring that the density during smelting is close to that of aluminum-based melt; during smelting, semi-solid stirring and high-power ultrasonic treatment are introduced to achieve SiC p Uniformly distributed in the melt. By comprehensively considering the alloying elements and SiC p The mechanism of the influence of content and size on mechanical properties was studied, and the large-scale preparation of high-strength, high-toughness and high-modulus aluminum-based materials was achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0025] Figure 1 Schematic diagram of the squeeze casting principle used in Example 1.

[0026] Figure 2 This is a macroscopic photograph of the aluminum-based composite ingot prepared in Example 1.

[0027] Figure 3It is a metallographic microstructure diagram of the aluminum-based composite material prepared in Example 1 and the original composition 6061 aluminum alloy prepared in Comparative Example 1 at 200 times.

[0028] Figure 4 The engineering stress-strain curves and modulus fitting curves of the aluminum alloy material samples prepared in Example 1 and Comparative Example 1 are shown.

[0029] Figure 5 These are the engineering stress-strain curves of the 6wt% SiC incremental aluminum-based composite material and the 10wt% SiC reinforced aluminum-based composite material in Comparative Example 2.

[0030] Figure 6 This is a graph showing the experimental results of Example 3 in which an aluminum-based composite material is prepared using a conventional stirring casting method.

[0031] Figure 7 It is a 200-fold metallographic microstructure diagram of the aluminum-based composite material prepared in Example 1, Comparative Example 2 and Comparative Example 4.

[0032] Figure 8 The engineering stress-strain curves of the aluminum-based composite materials prepared in Example 1, Comparative Example 2 and Comparative Example 4 are shown.

[0033] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0034] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0035] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0036] The Cu, Mg, Re (La / Ce=3 / 2), Zr elements and micron SiC added in the following examples and comparative examples are p 、Nano SiC p The quantities are all percentages of the mass of 6061 aluminum alloy ingots. The 6061 aluminum alloy ingots used were purchased from Southwest Aluminum; the product type is 6061 aluminum extruded bars; the implementation standards are GJB2504, GJB2920, and GJB3539.

[0037] The aluminum-based composite materials added with SiC ceramic particles prepared in the following examples and comparative examples are also called SiC-reinforced aluminum-based composite materials. The SiC ceramic particles used were purchased from Hefei Duoyile Trading Co., Ltd.

[0038] Embodiment 1:

[0039] The present embodiment provides a method for preparing a high-strength and high-modulus aluminum-based composite material, which uses a 6061 aluminum alloy ingot as a matrix aluminum alloy component, adds 4wt% Cu, 1wt% Mg, 0.5wt% Re (La / Ce=3 / 2), 0.2wt% Zr elements, and composites 5wt% micron SiC p With 1wt% nano-SiC p The specific preparation method is as follows:

[0040] Step 1: Prepare SiC p Composite preform with aluminum powder

[0041] SiC p The SiC p The mass ratio of SiC to aluminum powder is 1:4. p The mass ratio is 5:1 micron SiC p (average particle size 5um) and nano-SiC p (average particle size 50nm), the total volume of the material and grinding balls in the ball mill accounts for 2 / 3 of the volume of the ball mill. The high-energy ball milling process is: 220rpm, 15h, and rotate clockwise and counterclockwise every hour, with a rest period of 30min. p -Al mixed powder is pressed into a columnar block under 60MPa, and finally sintered in a vacuum furnace at 540℃ for 3h to obtain an aluminum-based composite material preform. Through this step, micro- and nano-SiC p Get effective dispersion and achieve SiC p Effective interface bonding with aluminum powder allows for smooth addition to the aluminum melt in subsequent operations.

[0042] Step 2: Preparation of aluminum matrix composite ingot

[0043] Under argon protection atmosphere, micron SiC p 、Nano SiC pThe mass fraction of 5wt% and 1wt% is 5wt% and 1wt%, and the prepared aluminum-based composite material preform is inserted into the bottom of a 6061 aluminum alloy ingot (the composition is shown in Table 2) and placed in a melting furnace, and Al-50Cu master alloy, pure Mg, Al-10Re master alloy, and Al-10Zr master alloy are added according to the addition amount of 4wt% Cu, 1wt% Mg, 0.5wt% Re (La / Ce=3 / 2), and 0.2wt% Zr elements, respectively. The melting furnace temperature is adjusted to 800℃ and the material is allowed to stand for 10min after it becomes molten. Subsequently, the temperature is lowered to 740-760℃ semi-solid range), and the semi-solid melt is stirred to make the added SiC particles evenly dispersed, the stirring speed is 600rpm, and the stirring time is 10min. Then the temperature was raised to 750℃, and the aluminum-based composite material melt was subjected to high-power ultrasonic vibration. The ultrasonic amplitude rod was located 2 cm below the liquid surface, the ultrasonic frequency was 20 kHz, the power was 3000 W, and the processing time was 10 min to achieve the addition of SiC p The aluminum matrix composite material is evenly distributed in the aluminum melt. Finally, the processed aluminum matrix composite material melt is cast in a mold preheated at 500°C for extrusion casting, and a high-strength, high-modulus aluminum matrix composite material ingot is obtained after demolding.

[0044] Squeeze casting is a conventional technology. The schematic diagram of squeeze casting is as follows Figure 1 As shown, it includes an upper punch 1, a half-mold 2 with an angled sheath, a graphite pad 3, an iron pad 4 and a blank 5. The upper punch can transfer the load to the blank and implement the pressure required for die casting; the angled sheath mold 2 supports the casting of aluminum liquid, and the angle and the half-mold facilitate the demolding; the graphite pad 3 is used to remove the gas in the die casting process on the one hand, and to prevent the aluminum liquid from directly contacting the mold, which makes demolding difficult and contaminates the blank and the mold on the other hand. The iron pad 4 limits the upward flow of the blank when the squeeze casting is applied. First, place a graphite pad at the bottom of the casting mold 2, spray a high-temperature release agent on the inner wall of the mold, preheat it at 500°C, and then cast the treated aluminum-based composite material melt into the mold 2, and then place the graphite pad and the iron pad 4 in turn, move the punch 1 downward at a speed of 200 mm / min, and when the punch contacts the iron pad, change the die-casting speed to 20 kN / s, the given pressure to 400 kN, and the holding time to 3 min; after the die-casting is completed, turn the mold 180°, use a press to press out the middle half-type mold 3, and then break it into two halves to obtain an aluminum-based composite material ingot. Figure 2 This is a macroscopic photograph of the prepared aluminum-based composite ingot.

[0045] The components with an actual content of matrix alloy greater than 0.1 wt % (excluding SiC ceramic particles) in the aluminum-based composite material ingot prepared in Example 1 were tested by ICP-MS, and the results are shown in Table 2.

[0046] Table 2

[0047]

[0048] In order to further demonstrate the beneficial technical effects of the present invention, the following control experiments were proposed, in which the 6061 aluminum alloy ingot raw material used was consistent with the composition in Example 1.

[0049] Comparative Example 1:

[0050] As a control experiment of Example 1, the difference relative to Example 1 is that on the basis of the composition of 6061 aluminum alloy, no additional Cu, Mg, Re (La / Ce=3 / 2), Zr elements and SiCp are added. The specific preparation process of Comparative Example 1 is as follows: In an atmosphere protected by argon, the 6061 aluminum alloy ingot is smelted in a smelting furnace at 800°C, and the ingot is allowed to stand for 10 minutes after melting. Subsequently, the temperature is lowered to 740-760°C, and the aluminum alloy melt is subjected to high-power ultrasonic vibration. The position of the ultrasonic amplitude rod is 2 cm below the liquid surface, the ultrasonic frequency is 20kHz, the power is 3000w, and the processing time is 10 minutes. Finally, the treated aluminum alloy melt is cast in a mold preheated to 500°C for extrusion casting, and after demolding, it is obtained as a 6061 aluminum alloy ingot. The extrusion casting process is consistent with that of Example 1.

[0051] Comparative Example 2:

[0052] As a control experiment of Example 1, this comparative example adopts the same preparation method as Example 1. The difference with Example 1 is that the content of SiCp added is changed, and only micron SiC is added. p (average particle size 5 um), and two groups of samples were prepared with contents of 6 wt% and 10 wt% respectively, and the rest of the process was the same as in Example 1.

[0053] Comparative Example 3:

[0054] As a control experiment of Example 1, compared with Example 1, the aluminum-based composite material was prepared by conventional stirring casting method, and all the material components and amounts thereof were consistent with those in Example 1. The specific process is as follows: in an argon atmosphere, the 6061 aluminum alloy ingot and the intermediate alloy of Cu, Mg, Re (La / Ce=3 / 2), and Zr elements were placed in a melting furnace at 800°C, and allowed to stand for 10 minutes after being fully melted. Then the temperature was lowered to 740-760°C, and an equal amount of aluminum powder and micron SiC as in Example 1 were added under mechanical stirring conditions. p (average particle size 5um) and nano-SiC p (average particle size 50 nm). Finally, the aluminum-based composite material melt is cast into a mold preheated at 500° C. for extrusion casting, and the aluminum-based composite material ingot is obtained after demolding. The extrusion casting process is the same as that of Example 1.

[0055] Comparative Example 4:

[0056] Compared with Comparative Example 3, this comparative example only changes the content of SiCp added. The content of SiC particles with an average particle size of 5 μm added in this comparative example is 10 wt %, and the rest of the process is the same as that of Comparative Example 3.

[0057] Figure 3 The metallographic microstructure diagrams are 200 times of the 6061 aluminum alloy and aluminum-based composite materials prepared in Comparative Example 1 and Example 1, respectively. It can be seen from the figure that, relative to the 6061 aluminum alloy, the grain size of the aluminum-based composite material prepared by the present invention is significantly refined, and the uniformity of the organization is significantly improved. The reason is: on the one hand, the introduction of micron SiC particles can serve as nucleation sites for grains and second phases, resulting in a significant reduction in grain size, and the second phase attaches to the SiC particles to form nuclei, reducing the segregation of the second phase at the grain boundary; on the other hand, the nano-SiC particles segregated at the grain boundary have a certain effect of pinning the grain boundary, hindering the growth of the grains. In addition, the added Zr element and Re (La, Ce) element are effective grain refiners, which can effectively segregate at the grain boundary to hinder the expansion of the grain boundary.

[0058] Figure 4 The engineering stress-strain curves of the 6061 aluminum alloy and the aluminum-based composite material prepared in Comparative Example 1 and Example 1 and the modulus fitting curve of the aluminum-based composite material are shown in FIG. Figure 4 (a) It can be seen that the tensile strength of the aluminum-based composite material and 6061 aluminum alloy prepared by the present invention are 230.5MPa and 152.8Mpa respectively, the yield strength is 115.8MPa and 80.7MPa respectively, and the elongation at break is 22.1% and 4.8%. Compared with 6061 aluminum alloy, the tensile strength, yield strength and elongation at break of the composite material prepared by the present invention are increased by 50.8%, 43.5% and 360.4% respectively, achieving the effect of synergistic improvement of strength and plasticity. Figure 4 (b) It can be seen that the elastic modulus of the aluminum-based composite material prepared by the present invention is as high as ∼116 GPa, which is ∼71% higher than the elastic modulus of ∼68 GPa of the commercial 6061 aluminum alloy.

[0059] Whether from Figure 3 The grain size of the microstructure, the uniformity of the microstructure, or Figure 4 The engineering stress-strain curve and modulus of the aluminum-based composite material prepared by the present invention all show a relatively high level, reflecting the advancement of the component design.

[0060] Figure 5The engineering stress-strain curves of the aluminum-based composite material with 6wt% micron SiC increment and the aluminum-based composite material with 10wt% micron SiC reinforcement in Comparative Example 2. It can be seen that with the increase of micron SiC content, the strength of the composite material increases. Therefore, in the subsequent comparative examples, only the aluminum-based composite material with 10wt% micron SiC reinforcement is used for comparison.

[0061] Figure 6 This is a graph showing the experimental results of preparing aluminum-based composite materials using conventional stirring casting method in comparative example 3. As can be seen from the figure, it is difficult to add nano-scale SiCp into aluminum melt using conventional stirring casting method, because nano-scale SiCp will float above the aluminum melt to form impurities during the smelting process.

[0062] Figure 7 It is a 200-fold metallographic microstructure diagram of the aluminum-based composite material prepared in Example 1, Comparative Example 2 and Comparative Example 4. Figure 7 (a) and (b) are metallographic schematic diagrams of (5um-5wt% + 50nm-1wt%) SiC reinforced aluminum-based composite material (Example 1) and (5um-10wt%) SiC reinforced aluminum-based composite material (Comparative Example 2), both of which are prepared by optimized stirring casting method. It can be seen from the figures that the (5um-5wt% + 50nm-1wt%) SiC reinforced aluminum-based composite material has a finer grain size and a more uniform SiC distribution. Figure 7 (c) is a schematic diagram of the metallographic structure of the (5um-10wt%) SiC reinforced aluminum-based composite material (Comparative Example 4) prepared by the conventional stirring casting method. It can be seen from the figure that the particle dispersion of the aluminum-based composite material prepared by the optimized stirring casting method is significantly enhanced, while the aluminum-based composite material prepared by the conventional stirring casting method has more agglomeration phenomena.

[0063] Figure 8 The engineering stress-strain curves of aluminum-based composite materials prepared in Example 1, Comparative Example 2 and Comparative Example 4 are shown in the figure. As can be seen from the figure, the (5um-5wt%+50nm-1wt%) SiC-reinforced aluminum-based composite material prepared by the optimized stirring casting method has similar yield strength, tensile strength and modulus compared to the (5um-10wt%) SiC-reinforced aluminum-based composite material, but shows a better elongation. The main reason is that the (5um-5wt%+50nm-1wt%) SiC-reinforced aluminum-based composite material has better organizational uniformity. Compared with the (5um-10wt%) SiC-reinforced aluminum-based composite material prepared by the conventional casting method, the aluminum-based composite material prepared after optimization has higher mechanical properties.

[0064] From the aspects of the microstructure and mechanical properties of the aluminum-based composite material, it can be seen that the (5um-5wt%+50nm-1wt%) SiC-reinforced aluminum-based composite material exhibits the best organizational uniformity and performance, reflecting the effectiveness of the SiC particle addition strategy of the present invention. In addition, compared with the conventional stirring casting method, the stirring casting optimization method proposed by the present invention can not only solve the problem of adding nano-scale SiC particles, but also achieve effective dispersion of SiC particles in the aluminum melt, which strongly proves the superiority of the stirring casting optimization method of the aluminum-based composite material proposed by the present invention.

[0065] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a high-strength, high-modulus aluminum-based composite material, characterized in that: The following steps are involved: S1, mixing SiC ceramic particles with aluminum powder, ball milling in a vacuum ball mill under an argon protective atmosphere, and then cold pressing and vacuum sintering to prepare an aluminum-based composite material precursor; The mass ratio of SiC ceramic particles to aluminum powder is 1:4 to 1:5, and the SiC ceramic particles are micron SiC with a mass ratio of 5:

1. p With Nano-SiC p ; S2. Under an argon protective atmosphere, the aluminum-based composite material precursor prepared in step S1, the 6061 aluminum alloy ingot, and the materials containing Cu, Mg, Re (La / Ce=3 / 2), and Zr elements are melted in a melting furnace at a temperature of 800° C. After becoming molten, the temperature is lowered to a semi-solid temperature range of 600-630° C. to obtain a semi-solid melt and stirred to fully and evenly disperse the SiC ceramic particles; then the temperature is raised to 740-760° C., and after the semi-solid melt is transformed into a molten state, the SiC ceramic particles are evenly distributed in the aluminum melt by ultrasonic vibration, and finally, high-strength, high-modulus aluminum-based composite materials are obtained by casting and die-casting; Among them, the added micron SiC p With Nano-SiC p They account for 5wt% and 1wt% of the 6061 aluminum alloy ingot respectively, and the added Cu, Mg, Re (La / Ce=3 / 2) and Zr elements account for 4wt%, 1wt%, 0.5wt% and 0.2wt% of the 6061 aluminum alloy ingot respectively. The Cu element is selected from Al-50Cu master alloy, the Mg element is selected from pure magnesium ingot, the Re element is selected from Al-10Re master alloy, and the Zr element is selected from Al-10Zr master alloy.

2. The method for preparing the high-strength and high-modulus aluminum-based composite material according to claim 1, characterized in that: In step S1, micron SiC p The particle size is 3-8um, nano SiC p The particle size is 40-80nm.

3. The method for preparing the high-strength and high-modulus aluminum-based composite material according to claim 1, characterized in that: In step S1, the parameters for ball milling SiC ceramic particles and aluminum powder are: rotation speed 220 rpm, time 15 hours, and alternating clockwise and counterclockwise rotation every hour, with a rest period of 30 minutes in between.

4. The method for preparing the high-strength and high-modulus aluminum-based composite material according to claim 1, characterized in that: In step S1, the cold pressing pressure is 60 MPa and the vacuum sintering temperature is 540°C.

5. The method for preparing the high-strength and high-modulus aluminum-based composite material according to claim 1, characterized in that: In step S2, the aluminum-based composite material precursor is placed at the bottom of the 6061 aluminum alloy ingot.

6. The method for preparing the high-strength and high-modulus aluminum-based composite material according to claim 1, characterized in that: In step S2, the stirring speed is 400 to 700 rpm.

7. The method for preparing a high-strength, high-modulus aluminum-based composite material according to claim 1, characterized in that: In step S2, ultrasonic vibration is performed using an ultrasonic horn.

8. The method for preparing the high-strength and high-modulus aluminum-based composite material according to claim 7, characterized in that: The ultrasonic horn is positioned 2 to 5 cm below the liquid surface, the ultrasonic frequency is 18 to 20 kHz, the power is 3000 W, and the treatment time is 5 to 10 minutes.

9. The method for preparing the high-strength and high-modulus aluminum-based composite material according to claim 1, characterized in that: In step S2, the pressure of the die-casting process is 400 kN, and the holding time is 2 to 5 minutes.

10. A high-strength, high-modulus aluminum-based composite material, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for strengthening and toughening metal-based composite material

    CN103436728A

  • Method for preparing nano-aluminum-nitride reinforced aluminum-based composite semi-solid slurry based on ultrasonic and mechanical vibration combination

    CN104532046A

  • Manufacturing method of aluminum alloy rivet wire for aerospace

    CN105274408A

  • Method for preparing SiC particle reinforcement aluminum matrix composite material through tableting pretreatment

    CN106244841A

  • Forming method for nano particle reinforced aluminum-based composite material

    CN107604193A